1969
DOI: 10.1136/adc.44.233.88
|View full text |Cite
|
Sign up to set email alerts
|

Adrenocortical response to stress in newborn infants.

Abstract: More than half of the deaths occurring under the age of 12 years take place during the first week of life, and the term 'biochemical death' is sometimes used where an adequate pathological explanation cannot be found at necropsy. Following the pioneer work of Selye (1936), which drew attention to the prominent role of the adrenal cortex in the endocrine response to stress, it became established that an increased secretion of corticosteroids occurred in adults under conditions of stress, and that, in some unkno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

1971
1971
1993
1993

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…Again it can be speculated that postnatal adaptation in the first 12 h of life is less stressful in SGA infants or that the adrenal cortex is not able to react adequately to stress. Two earlier studies (23,24) of adrenal function in intrauterine growth-retarded infants have shown abnormal cortisol secretion rates and a decreased steroid response to stress, whereas Reynolds et al (25) reported a normal cortisol response to ACTH stimulation in intrauterine growth-retarded infants. Hypoglycemia, a frequent condition in SGA infants, can be excluded as a possible factor influencing adrenal steroid response, because normoglycemia was maintained in all infants by initial intravenous glucose followed by early oral glucose supply.…”
Section: Discussionmentioning
confidence: 97%
“…Again it can be speculated that postnatal adaptation in the first 12 h of life is less stressful in SGA infants or that the adrenal cortex is not able to react adequately to stress. Two earlier studies (23,24) of adrenal function in intrauterine growth-retarded infants have shown abnormal cortisol secretion rates and a decreased steroid response to stress, whereas Reynolds et al (25) reported a normal cortisol response to ACTH stimulation in intrauterine growth-retarded infants. Hypoglycemia, a frequent condition in SGA infants, can be excluded as a possible factor influencing adrenal steroid response, because normoglycemia was maintained in all infants by initial intravenous glucose followed by early oral glucose supply.…”
Section: Discussionmentioning
confidence: 97%
“…Some possible parallels may be drawn between the relative infrequency of histological stress in infants of low birthweight, and a temporary lack of a response to cold stress in infants of low birthweight (Hey and Katz, 1969) and diminished steroid production in infants of low birthweight (Cathro et al, 1969). Clearly a great deal of useful information might be gained by undertaking studies to compare endogenous steroid production in the fetus with pulmonary compliance and, in those infants who do not survive to compare adrenal histology at necropsy with pulmonary pressure or volume curves.…”
Section: Discussionmentioning
confidence: 99%
“…Stress has been reported to increase serum cortisol [11] and free urinary cortisol levels [12] in preterm infants during the first 5 days of life. High corti sol values have been reported in single blood sample mea surements in neonates with perinatal asphyxia [13], RDS [12,14,15], intraventricular hemorrhage [16], patent duc tus arteriosus and pneumothorax [17],…”
Section: Discussionmentioning
confidence: 99%